2014
DOI: 10.1152/ajpregu.00071.2014
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and cellular localization of ROMKs in the gills and kidney of Mozambique tilapia acclimated to fresh water with high potassium concentration

Abstract: Regulation of plasma K(+) levels in narrow ranges is vital to vertebrate animals. Since seawater (SW) teleosts are loaded with excess K(+), they constantly excrete K(+) from the gills. However, the K(+) regulatory mechanisms in freshwater (FW)-acclimated teleosts are still unclear. We aimed to identify the possible K(+) regulatory mechanisms in the gills and kidney, the two major osmoregulatory organs, of FW-acclimated Mozambique tilapia (Oreochromis mossambicus). As a potential molecular candidate for renal K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
4
21
0
Order By: Relevance
“…5C, G, K) immunosignals were detected in apical membrane, and NKA (Figs. 5B, F, J) was in basolateral membrane of the ionocytes, consistent with previous observations (Furukawa et al, 2014). Notably, ionocytes of the gills incubated in H-K medium tended to show stronger signals of ROMKa than those in the control medium (Fig.…”
Section: Experiments 2 In Vitro Effects Of K + Concentration On Romkasupporting
confidence: 91%
See 2 more Smart Citations
“…5C, G, K) immunosignals were detected in apical membrane, and NKA (Figs. 5B, F, J) was in basolateral membrane of the ionocytes, consistent with previous observations (Furukawa et al, 2014). Notably, ionocytes of the gills incubated in H-K medium tended to show stronger signals of ROMKa than those in the control medium (Fig.…”
Section: Experiments 2 In Vitro Effects Of K + Concentration On Romkasupporting
confidence: 91%
“…In the kidney, renal outer medullary K + channel (ROMK) is expressed in apical membrane of tubule cells from the thick ascending limb (TAL) through the outer medullary collecting duct (OMCD), and its expression mainly affects K + excretion (Hebert et al, 2005). Historically, the mechanisms by which teleosts regulate plasma K + have been largely unknown; however, we recently found that ROMKa expressed in gill ionocytes is the primary pathway for K + regulation in tilapia (Furukawa et al, 2012(Furukawa et al, , 2014. Thus, in both mammals and teleosts it now appears that ROMK mediates K + homeostasis (Wang and Giebisch, 2009;Furukawa et al, 2012Furukawa et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this model focuses on Na + uptake, this must also be coordinated with the transport of other ions to maintain effective electrochemical gradients. For example, it was recently discovered that Omoss excretes K+ in both fresh and seawater, facilitated by apical potassium channels (Kir) [61], and we observed that several paralogs of Kir ( KCNJ ) were down-regulated, consistent with increased ion conservation in blackwater (Figure 3; Supplemental Tables 2 and 3). These authors also speculated that K + may be excreted through K + -Cl − co-transporters (KCC1, KCC4), but we noted these paralogs were up-regulated ( SLC12A4, SLC12A7 ), suggesting they may actually play a role in K + /Cl − uptake or recycling.…”
Section: Discussionsupporting
confidence: 55%
“…Versions of this model are supported by experimental evidence, yet many questions remain. For example, in Omoss Na + and Cl − uptake occurs through mitochondria-rich cells (MRC) that express partially exclusive sets of ion transporters (“NHE” or “NCC” MRC), but many of these transporters move overlapping sets of ions (Na + , K + , Ca 2+ , Cl − , HCO 3 − ) to energize critical gradients, and their division and coordination have not been clarified [61]. Moreover, it remains to be resolved if this Na + /NH 4 + exchange model is effective in acidic, ion-poor environments, where the external [H + ] and [Na + ] are extremely unfavorable for exchange [62].…”
Section: Discussionmentioning
confidence: 99%